Properties of steel fiber reinforced concrete with different length of steel fiber - Nik Suharliza Binti Nik Zol (School of Environmental Engineering, University Malaysia Perlis, 2014)
Currently in concrete technology is booming to improve the quality and properties of concrete. There are various additives that can strengthen the concrete. Additional materials include the use of steel fibers into the concrete mix. With the used of steel fibers it can enhance the strength of the concrete. Tests have been conducted on the properties of steel fiber reinforced concrete with different percentages of steel fibers to obtain high compressive strength.